Photovoltaic properties of Bi2FeCrO6 films epitaxially grown on (100)-oriented silicon substrates. Issue 6 (22nd January 2016) - Nechache, R.; Huang, W.; Li, S.; Rosei, F.
Abstract : We demonstrate the promising potential of using perovskite Bi2 FeCrO6 (BFCO) for niche applications in photovoltaics (PV) ( e.g. self-powered sensors that simultaneously exploit PV conversion and multiferroic properties) or as a complement to mature PV technologies like silicon. Abstract : We demonstrate the promising potential of using perovskite Bi2 FeCrO6 (BFCO) for niche applications in photovoltaics (PV) ( e.g. self-powered sensors that simultaneously exploit PV conversion and multiferroic properties) or as a complement to mature PV technologies like silicon. BFCO thin films were epitaxially grown on silicon substrates using an MgO buffer layer. Piezoresponse force microscopy measurements revealed that the tensile strained BFCO phase exhibits a polarization predominantly oriented through the in-plane direction. The semiconducting bandgap of the ordered BFCO phase combined with ferroelectric properties, opens the possibility of a ferroelectric PV efficiency above 2% in a thin film device and the use of ferroelectric materials simultaneously as solar absorber layers and carrier separators in PV devices. A large short circuit photocurrent density of 13.8 mA cm −2 and a photovoltage output of 0.5 V are typically obtained at FF of 38% for BFCO devices fabricated on silicon. We believe that the reduced photovoltage is due to the low diffusion length of photogenerated charge carriers in the BFCO material where the ferroelectric domains are predominately oriented in-plane and thus do not contribute efficiently to the photocharge separation process.